2022
DOI: 10.3389/fmats.2022.946163
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Beam Manipulations by Reconfigurable Intelligent Surface With Independent Control of Amplitude and Phase

Abstract: Reconfigurable intelligent surfaces (RISs) have attracted extensive attention in recent years due to their strong ability to improve and customize electromagnetic wave propagation channels in wireless communications. In this article, we propose a design procedure for an RIS and its programmable element, whose reflection phase and amplitude can be jointly controlled by adjusting the states of the varactor and PIN-diode. In addition, by introducing metallic vias in the RIS element, the programmable element can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The preceding research works [20][21][22], as well as our proposed RAPM, achieved dynamic-control-reflected EM beams by incorporating active diodes integrated within the upper passive metal layer. The differences between our study and the previous works [20][21][22] in the structures and performance are shown in Table 1. RAPM operates normally in the 10.5-11.5 GHz band, basically covering the 11 GHz band in microwave communication systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preceding research works [20][21][22], as well as our proposed RAPM, achieved dynamic-control-reflected EM beams by incorporating active diodes integrated within the upper passive metal layer. The differences between our study and the previous works [20][21][22] in the structures and performance are shown in Table 1. RAPM operates normally in the 10.5-11.5 GHz band, basically covering the 11 GHz band in microwave communication systems.…”
Section: Discussionmentioning
confidence: 99%
“…The metasurface proposed in [20] has the ability to regulate the quantities of reflected EM beams in 1-D space, while the distribution of EM waves' energy is limited. The proposed metasurface in [21] can divide the vertically incident waves into two lobes with distinct elevation angles (θ) and power intensities. Regarding the metasurface described in [22], it is able to modulate the quantities of reflected EM beams in 1-D space, including the suppression of the sidelobes of the scattering beam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Z s is the impedance of the dielectric substrate and can be equated to a short transmission line [26], related to the dielectric substrate material and thickness (ε r and h):…”
Section: Discussion and Theoretical Analysismentioning
confidence: 99%
“…To achieve reconfigurable magnitude and phase control, active components, such as PIN and varactor diodes [24], and graphene [25], to name a few, are mainly used. A reconfigurable metasurface reflector based on two varactor diodes was recently proposed in [26] with a demonstration of simultaneous and independent magnitude and phase control for single-plane beamforming.…”
Section: Introductionmentioning
confidence: 99%